In vitro and in silico analysis of dual-function peptides derived from casein hydrolysate - Maolin Tu; Xinyu Qiao; Cong Wang; Hanxiong Liu; Shuzhen Cheng; Zhe Xu; Ming Du (Food Science and Human Wellness)
There is no study on food-derived peptide with both anticoagulant and angiotensin I-converting enzyme inhibitory (ACEI) activities yet. In this work, the anticoagulant and ACEI activities of the casein hydrolysates released by pepsin digestion were evaluated for the first time to the best of our knowledge. Results indicated that the casein hydrolysate exhibited potent anticoagulant activity by prolonging the thrombin time (TT) and the activated partial thromboplastin time (APTT). Compared with control samples, at 10 mg/mL, the TT and APTT of casein hydrolysate were 186.0 % ± 6.6 % and 163.5 % ± 7.4 %, respectively. The casein hydrolysate also showed a strong ACEI activity with an IC50 value of 1.775 mg/mL. The components of the bioactive casein hydrolysate were analyzed by nanoscale liquid chromatography quadrupole time-of-flight tandem mass spectrometry (NanoLC-Q-TOF-MS/MS). Total of 115 peptides were identified, among which 34, 9, 55 and 17 peptides were derived from αs1-, αs2-, β-, and κ-casein, respectively. The results of PeptideRanker and PepSite 2 analysis showed that 6 peptides (FRQFYQL, NENLLRF, NPWDQVKR, PVVVPPFLQ, PVRGPFPIIV, and ARHPHPHLSF) have both ACEI and anticoagulant activities by binding to the active sites of ACE and thrombin. This study indicated that casein is a potential functional food supplement that can be used for medical purposes.